Role of PCR method using IS6110 primer in detecting Mycobacterium tuberculosis among the clinically diagnosed childhood tuberculosis patients at an urban hospital in Dhaka, Bangladesh. (March 2018) - Kabir, Senjuti; Uddin, Mohammad Khaja Mafij; Chisti, Mohammod Jobayer; Fannana, Tilka; Haque, Mohammad Enamul; Uddin, Muhammad Reaj; Banu, Sayera; Ahmed, Tahmeed
Highlights: The lack of accurate diagnostic methods hampers the diagnosis of childh tuberculosis (TB). This study evaluated the performance of smear microscopy, solid and liquid cultures, and PCR using IS 6110 primers for the detection of Mycobacterium tuberculosis (MTB) among clinically diagnosed paediatric TB patients. MTB was detected more often by IS 6110 PCR method than by smear microscopy and culture techniques among clinically diagnosed child TB patients. IS 6110 PCR can be applied as a rapid screening test for the detection of child TB. Larger scale studies are recommended to determine the diagnostic efficacy of IS 6110 PCR in improving the detection of child TB. Abstract: Objective: Better methods are needed for the accurate detection of child tuberculosis (TB). This study compared different laboratory tests and evaluated IS 6110 PCR for the detection of Mycobacterium tuberculosis (MTB) among clinically diagnosed child TB patients. Methods: A total of 102 paediatric patients (<15 years old) with clinically diagnosed TB were enrolled in this study. The patients were admitted to the icddr, b hospital in Dhaka between 2003 and 2005. Sputum/gastric lavage samples were collected for smear microscopy, culture (solid/Lowenstein–Jensen medium and liquid/MGIT), and IS 6110 PCR testing. The sensitivity, specificity, and positive and negative predictive values (PPV, NPV) of smear microscopy and PCR were compared to the two culture methods. Results: Three patients were positive on smear microscopy (2.9%). MTB was detected by conventional culture in 15.7% (16/102), liquid culture in 14% (14/100), and IS 6110 PCR in 61.8% (63/102). PCR detected an additional 45 patients who were undetected with the three other tests. Compared to conventional and liquid culture, respectively, smear microscopy showed sensitivity of 18.8% and 21.4%, specificity of 100% individually, PPV of 100% individually, and NPV of 86.9% and 88.7%, whereas PCR had sensitivity of 87.5% and 92.9%, specificity of 43% individually, PPV of 22.2% and 21%, and NPV of 94.9% and 97.4%. Conclusions: PCR can be useful compared to smear microscopy and culture methods and is applicable as a rapid screening test for child TB. A larger scale study is required to determine its diagnostic efficacy in improving the detection of child TB in the presence and absence of severe malnutrition.